(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
In Nigeria most of the small-scale agroforestry farmers does not have access to formal credit which greatly have negative impact on their productivity which brings about low yield resulting in low income to the farmers. Agricultural credit enhances productivity and promotes standard of living by breaking vicious cycle of poverty of small-scale farmers participating in agroforestry practices. The study therefore assessed the impact of formal credit on the productivity of small-scale farmers in Kaduna state, Nigeria. A multistage sampling technique was used to collect data from 250 agroforestry farmers (beneficiaries and non-beneficiaries of formal credit). Primary data were generated using a well-structured questionnaire. Descriptive statistics, probit model regression and inferential statistics were used to analyze the data collected and test the hypothesis. The study revealed majority (52.40%) of the sampled respondents are within the productive age bracket with a mean age of 44 years. The analysis of the level of education show that majority of the respondents (95.5%) attended one level of education or another. The study also revealed that all the prospective borrowers must have an account with the bank and must have maintained the account for a minimum period of six months before applying and being considered for a loan facility. The result of the probit analysis revealed that farming experience and age were the only two factors that had direct and significant (P<0.1) relationship with the probability of farmers’ participation in agroforestry practices in the study area. Chow Test revealed that F- calculated is higher than...